Self-administration of omalizumab: why not? A literature review and expert opinion. (3rd April 2021) - Menzella, Francesco; Ferrari, Emanuele; Ferrucci, Silvia Mariel; Lombardi, Enrico; Alfano, Silvio; Bonavita, Ornella; Morini, Paolo; Rizzi, Andrea; Matucci, Andrea
ABSTRACT: Introduction : Omalizumab is used to treat severe uncontrolled allergic asthma and chronic spontaneous urticaria (CSU), and is approved for self-administration in prefilled syringes. It is thus important to understand the advantages, critical issues, and indications for home administration. Areas covered : The present review summarizes the available evidence on home administration of omalizumab in asthma and CSU to illustrate the advantages derived from self-administration of patients in this setting. Expert opinion : The available data suggest that patients can safely administer biologics at home with suitable training, and that home administration is time saving and cost-effective. The majority of patients with severe asthma or CSU treated with omalizumab are likely to be suitable candidates for self-administration, which can be proposed to anyone that the clinician deems suitable. In addition to clinicians, pharmacists can also play a key role in managing patients who are prescribed home administration. A practical flow chart is proposed on selection of patients and their management during home administration. Self-administration of biologics can be considered as a valid alternative to traditional injections in a clinical setting, and the evidence has shown that no major issues need to be overcome in terms of safety or efficacy.